Watermarked and Noisy Images identification Based on Statistical Evaluation Parameters - Sadkhan, Sattar B.; Abbas, Nidaa A. (Sulaimani Journal for Pure and Applied Sciences, 2013)
A watermark scheme is an important technique for copyright protection of digital images. Digital watermarking is the process of computer-aided information hiding in a carrier signal. The main interest of this paper is copyright protection, and it takes into consideration four important aspects: (i) Implementation the images watermarking by Least Significant Bit method (LSB) for JPEG gray images using invisible watermark, (ii) Evaluation the watermarking images using different statistical parameters, (iii) Identifying watermark images from noisy images by showing that the difference in results using open set identification, (iv) Proposing threshold equations that can be used to differentiate among noisy and watermarked images based on the used statistical parameters of the tested images. By comparing the image quality, obtained by the proposed method with the calculated statistical metrics like Variance, Standard Deviation, Kurtosis and Skewness. The results are promising and give us a great indication to differentiate between the images of watermarking and noisy images.
Keywords: Watermarking image copyright Identification Statistical Metrics